PENGARUH JOB INSECURITY DAN KERJA STRES TERHADAP TURNOVER INTENTION PADA KARYAWAN PT SOLID GOLD BERJANGKA MAKASSAR - Risman; Nursyafika (Paser Institute Management and Busines, 2024)
The aim of this research is to find out whether job insecurity influences employee Turnover Intention at PT. Solid Gold Futures Makassar. To find out whether work stress has an effect on PT. Solid Gold Futures Makassar. To find out how job insecurity and work stress both influence Turnover Intention at PT. Solid Gold Futures Makassar. The analytical collection method used in this research is a quantitative method. Data collection methods used questionnaires and direct observation with 157 respondents. The test results using the validity test, reliability test and multiple regression test show that the research model is feasible. Furthermore, using the f test, t test and R test show that job insecurity and work stress have a significant and positive effect on turnover intention decisions. Data analysis used SPSS version 25 path analysis. Based on the results of partial hypothesis measurements, it was found that Job Insecurity had a positive and insignificant effect on turnover intention and Job Stress had a positive and significant effect on Turnover Intention at PT. Solid Gold Berjangka Makassar and simultaneously job insecurity and work stress both have a positive and significant effect on turnover intention.